What Can We Learn From COVID-19 Protocols With Regard to Management of Nonoperative Pediatric Orthopaedic Injuries?. Issue 8 (September 2021) - Hancock, Graeme E.; Baxter, Ian; Balachandar, Vivek; Flowers, Mark J.; Evans, Owain G.
Abstract : Introduction: The COVID-19 pandemic has resulted in significant changes to normal practice in pediatric outpatient orthopaedics, with the instigation of telephone fracture clinic appointments, and the use of self-removable casting. We aim to determine any beneficial or detrimental short-term effects of these changes. Methods: All patients referred to fracture clinic from the emergency department during the period March 24, 2020 to May 10, 2020 (national lockdown) were assessed for number of face to face and telephone appointments, number of radiographs performed, time to discharge, use of a removable cast, any cast complications, other complications, reattendance or re-referral after discharge. They were compared with patients referred in the same period in 2019. Follow-up was to 6 months for every patient. Results: In 2019, 240 patients were reviewed and 110 in 2020. Changes in practice resulted in significant differences in the number of face to face appointments per patient [2 (1 to 6) 2019 vs. 1 (0 to 5) 2020 ( P <0.00001)] and increase in telephone appointments [0 (0 to 1) 2019 vs. 1 (0 to 2) 2020]. Number of radiographs per patient [1 (1 to 7) 2019 vs. 1 (1 to ) 2020 ( P =0.0178)] and time to discharge [29 d (0 to 483) 2019 vs. 16 d (0 to 216) 2020 ( P <0.00001)] also reduced significantly. Use of a self-removable casting technique increased significantly (2.4% of casts in 2019 vs. 91.8% in 2020 ( P <0.00001). There were no significant differences in complications related to cast or otherwise, unplanned attendance or reattendance after discharge. Use of self-removable casts for supracondylar fractures and for simple injuries (including distal radius, forearm, Toddler's, and ankle fractures) also demonstrated no change in complication rate. Significant potential cost savings of >£185 000 per annum could be demonstrated through clinic appointment and cast removal reductions. Discussion: Changes to the normal management of pediatric orthopaedic trauma brought about by the COVID-19 pandemic have been demonstrated to be safe in the short term with no increase in complications demonstrated. Potential cost savings are possible both to the health care provider and also to the patient because of reduced hospital attendance. It is feasible to continue these practices for the potential benefits as they appear safe in the short term. Level of Evidence: Level III—therapeutic study—retrospective comparative study.